Leukocyte count and C reactive protein as diagnostic factors in febrile convulsion - Garima Biyani (Asian Journal of Medical Sciences, 2017)
Background: Febrile convulsion (FC) is the most common seizure disorder in childhood. White blood cell (WBC) and C reactive protein (CRP) are commonly measured in FC. Add a paragraph on Aims and Objectives of the study.